The Possibilities and Limits of “Co-producing” Research - Paylor, Jonathan; McKevitt, Christopher (Frontiers in Sociology, 2019)
In this perspective paper, we explore the growing enthusiasm for ‘co-produced’ research, focusing in particular on the United Kingdom’s National Institute for Health Research’s recent adoption of the term co-production. We consider how this interest in co-production is driven by concerns that patient and public involvement (PPI) in health research tends to be ‘tokenistic’ and to reproduce power imbalances between researchers and lay contributors. We argue that these apparent implementation ‘barriers’ or ‘inconsistencies’ need to be understood in relation to the various elements that the institutionalisation of PPI brings together. We show how these elements are articulated in such a way that consumer, managerial and performative logics and practices are dominant, resulting in limits being placed on the scope and forms of PPI, and the emergence of acts of recalcitrance and impression management. By considering the alternative discursive repertoires made available through co-production, we point to the possibilities co-production presents for moving beyond these dominant tendencies. We argue, however, that such possibilities need to be understood in relation to the constraints of the present. In doing so, we draw attention to the tenacity of the articulations that have historically constituted the institutionalisation of PPI.